Knowledge, Attitudes, and Behaviors among Office Workers about COVID-19 Prevention - Masruroh, Nur Lailatul; Pradani, Vega Tyas; Pemiluwati, Tri; Melizza, Nur; Prasetyo, Yoyok Bekti; Kurnia, Anggraini Dwi (Gaceta Médica de Caracas, 2022)
The number of positive cases of COVID-19 in office clusters makes the government implement health protocols that are useful to prevent exposure to COVID-19 while working. Health protocols are self-protection measures to prevent COVID-19 transmission. Health protocol measures include washing hands, maintaining distance, and avoiding crowds. This study aimed to identify knowledge, attitudes, and preventive behaviors in office workers about preventing COVID-19.